Usability Study Of Integrated Rula-Kinect System For Work Posture Assessment - Ahmad, Nadiah; Halim, Isa; Radin Umar, Radin Zaid; Jamli, Mohamad Ridzuan; Syed Mohamed, Muhammad Syafiq; Albawab, Tarek Mhd Moataz; Abdullah, Muhammad Haziq Lim; Padmanathan, Vinothini (Penerbit UTHM, 2018)

(untitled)
A good work posture is one of vital contributors to occupational health and to increase the efficiency of industrial workers.Recently,numerous research works have developed an Integrated RULA- KinectTM system for work posture assessment;however,usability of the developed system remains unknown.The objective of this study was to develop a prototype of Integrated RULA-KinectTM system. Additionally,this study performed usability testing on the Integrated RULA-KinectTM system and RULA Employee Assessment Worksheet to determine feedbacks and reactions from the potential users.A focus group session was conducted among eight potential users,which divided into 2 groups (novice and expert).The results of the focus group session revealed that both novice and expert users agreed that the Integrated RULA-KinectTM system is easy to use compared to RULA Employee Assessment Worksheet. This study concluded that the Integrated RULA-KinectTM system is able to counter some limitations of the RULA Employee Assessment Worksheet.